Teaching Reform on Digital Circuit and Logic Design Course - Wang, Zhonghua; Hu, Shijie (American Journal of Education and Learning, 2017)
Owning strong theoretical and practical performance, the “digital circuit and logic design” course plays a vital role in the electronic information speciality. Although the digital circuit and logic design course emphasizes the practical characteristics, there still ignores the linking with other courses in teaching process. In this paper, the teaching reform program is put forward by the project-driven methods to embody the course characteristics of the engineering application, then the course teaching reform indicates that it can better stimulate the students’ learning interest, train the students’ creative thinking and improve the students’ entrepreneurial ability, then train the excellent electronic information talents.